La protection des infrastructures critiques – défis actuels - Dan Fifoiu (Romanian Journal of European Affairs, 2010)
Considering that in the European Union’s plan, it has not been identified a solution for surpassing the legal differences between states (derived from priorities and different interests), Romania continues the program of alignment towards increasing its own standards and interconnecting internal critical infrastructures with the European and regional ones. This process is a lasting one, fact revealed also by the distance, in terms of time, between the first approaches, at a European level, of the problems of critical infrastructures, at the implementation of Directive 114/2008 provisions. The steps taken by the authorities in Bucharest are intended to drive Romania towards a level of development compatible both with the integration in a single European space of critical infrastructures and the fulfillment of an important role in stating the future strategies of the European Union. Currently, Romania’s alignment to the European Union and international standards creates the optimum framework for developing and implementing some specific provisions which, at this time, are materialized as the steps of a single national plan for protecting critical infrastructures, on the way of being configured.